Buckling and vibrations of the shell with the hole under the action of thermomechanical loads - Bazhenov, V. A.; Krivenko, O. P. (КНУБА, 2020)
The paper outlines the fundamentals of the method of solving static problems of geometrically nonlinear deformation, buckling, and vibrations of thin thermoelastic inhomogeneous shells with complex-shaped midsurface, geometrical features throughout the thickness, under complex thermomechanical loading. The technique is based on the geometrically nonlinear equations of three-dimensional thermoelasticity, the finite element formulation of the problem in increments, and the use of the moment finite-element scheme. A thin shell is considered by this method as a threedimensional body. We approximate a shell by one spatial universal finite element (FE) throughout the thickness. The universal FE is based on an isoparametric spatial FE with polylinear shape functions for coordinates and displacements. The universal element has additional variable parameters introduced to expand its capabilities. The method of modal analysis of the shell is based on an approach that at each current stage of thermomechanical loading takes into account the stresses accumulated at the previous stages. The developed algorithm allows one to study geometric nonlinear deformation and buckling of elastic shells of an inhomogeneous structure with a thin and medium thickness, as well as to study small vibrations of the shells relative to the reference deformed state caused by static loading, taking into account large displacements and a prestressed state. An analysis of the stability and vibration of the spherical panel with the hole is carried out. The effect on the frequencies and mode shapes of the shell of the sequential action of thermal and mechanical loads is investigated.
Втрата стійкості та коливання оболонки з отвором під дією термосилового навантаження
Потеря устойчивости и колебания оболочки с отверстием под действием термосиловой нагрузки
Keywords: elastic shell; hole; buckling; natural frequency; mode shape; thermo-mechanical load; universal finite element; пружна оболонка; отвір; втрата стійкості; власна частота; форма коливань; термосилове навантаження; універсальний скінченний елемент; упругая оболочка; отверстие; потеря устойчивости; собственная частота; форма колебаний; термосиловая нагрузка; универсальный конечный элемент; 539.3; 624.074.4